2017
DOI: 10.3892/mco.2017.1433
|View full text |Cite
|
Sign up to set email alerts
|

Low uric acid level increases the risk of infectious mononucleosis and this effect is more pronounced in women

Abstract: Abstract. Infectious mononucleosis (IM) due to Epstein-Barr virus infection is common. Uric acid (UA) is an important endogenous antioxidant. To the best of our knowledge, the association between UA and IM has not been comprehensively investigated to date. The aim of the present study was to investigate this association in Chinese patients. A total of 95 patients (47 men and 48 women) with IM were recruited, along with 95 healthy controls. Clinical data were classified by patient sex. Receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, few studies on associations between serum uric acid concentrations and infections have been previously reported. Hypouricemia is a poor prognostic indicator in patients with intra-abdominal sepsis (36) or radiating pneumonitis (37). Another study showed that hypouricemic patients with SARS had poorer outcomes, especially in terms of respiratory failure (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies on associations between serum uric acid concentrations and infections have been previously reported. Hypouricemia is a poor prognostic indicator in patients with intra-abdominal sepsis (36) or radiating pneumonitis (37). Another study showed that hypouricemic patients with SARS had poorer outcomes, especially in terms of respiratory failure (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, uric acid crystals can be sensed by Clec12A, a regulator of type-I interferon responses, which is a pivotal defensive mechanism against viral infection ( 33 ). Uric acid strongly enhances T-cell immune responses to viruses ( 34 ), and low uric acid concentrations increase the risk of infection with viruses, such as Epstein–Barr virus ( 35 ). However, few studies on associations between serum uric acid concentrations and infections have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 32 found that low UA levels were predictive of infectious | 3927 mononucleosis, particularly in women. More recently, Hu et al 33 indicated that UA levels were decreased and negatively associated with COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that decreased UA levels exist in many viral pathogens such as influenza virus, hepatitis virus, respiratory viruses, and Epstein–Barr virus‐associated viral diseases. Zhang et al 32 found that low UA levels were predictive of infectious mononucleosis, particularly in women. More recently, Hu et al 33 indicated that UA levels were decreased and negatively associated with COVID‐19 severity.…”
Section: Discussionmentioning
confidence: 99%